Comparison on free-living nematode compositions of the Cau, Day, Cam and Nhue rivers - Thu, Nguyen Thi; Thanh, Nguyen Vu (Academia Journal of Biology, 2014)
Free-living nematodes in fresh water habitats in Vietnam were studied recently. In connection with the creation of new database for the biological monitoring assessment of water quality from the watercourse surface of all rivers and the wetland ecosystems, during 2002-2005 years, the aquatic nematodes fauna of the Cau, Day, Cam and Nhue rivers had been investigated. 144 free living nematode species belonging to 51 families of 9 orders were identified from samples collected in these four rivers. The level of species diversity has been shown in all most sampling habitats with 85 species in Cau river; 76 species in Day river; 52 species in Nhue river. In the Cam river, only 22 species have been found. These nematode species could be divided into three principal ecological groups: fresh-water group, saline-water group and terrestrial-phytoparasitic group. Five nematode species were found in all these four river ecosystems: Eucephalobus oxyuroides, Rhabdolaimus terrestric, Daptonema dihystera, Terschellingia elegans and Tylenchus sp. The Cau river had the greatest nematode species number and nematode individual number. The species Paraplectonema vietnammicum dominated in samples from the Cau and Day rivers. The rhabditid species Panagrolaimus paetzoldi was numerously occurred in the collecting samples from the Nhue river and the reason was caused by the waste domestic and industrial discharge from population centers and manufactures in the riverbank into the river flow. The Cam river was very poor in species and specimens.